La invención de la diferencia costarricense, 1810-1870 - Acuña Ortega, Víctor Hugo (Revista de historia., 2002)
In this article the author traces the process of formation of the principal attributes of the Costa Rica nation, and determines which were the meanings of belonging in Costa Rica in the period 1810-1870.